An indacenodithiophene core moiety for organic solar cells. (29th September 2021) - Siddiqui, Afzal; Suman,; Singh, Surya Prakash
Abstract : Indacenodithiophene (IDT) is widely employed in photoactive materials for OSC devices with the highest efficiency of 12%. IDT-based molecules show excellent light harvesting efficiency, charge transportation ability and molecular packing. Abstract : Organic solar cell (OSC) is an important device that harvests solar energy and converts it into electrical energy using organic conjugated molecules as photoactive materials. Appreciable research efforts have been performed during the last few decades to develop novel photoactive materials and employ different designed device architectures and fabrication processes to improve the performance of OSCs. Different types of donor (simple/ladder-type) and acceptor units can be used to design and synthesize new photoactive materials and further molecular engineering can be performed to enhance the optoelectronic properties of these materials. Ladder-type units (those having fused four or more conjugated rings), such as indacenodithiophene (IDT), indolocarbazole (ICz), indaceno-[3, 2- b ]-thiophene (IDTT) and benzo[1, 2- b :4, 5- b ]dithiophene (BDT), can be introduced as donor units to construct photoactive materials. IDT is a rigid, coplanar π-conjugated unit containing five fused rings. Different types of IDT-core-based light harvesting materials have been developed for OSCs and a power conversion efficiency of 12% has been attained. Until now, only one review on indacenodithiophene-based polymer solar cells was available in the literature and it discussed the factors affecting the band gaps and film morphologies of IDT-based molecules. In contrast, this review article examines the recent research done in the area of IDT-based materials for use in OSCs. The impact of different kinds of donor/acceptor units on the overall performance of IDT-based materials is also discussed. Additionally, we discuss the effects of alkyl/aryl side chains on the optoelectronic and photovoltaic performance of IDT materials.